Preconception women's views of promoting preconception women's health in Australia. (12th September 2020) - Walker, Ruth; Drakeley, Shelia; Boyle, Jacqueline
Abstract: Issue addressed: Sub‐optimal lifestyle choices made long before pregnancy have the potential to impact negatively maternal health and pregnancy outcomes. However, many women are unaware of this and do not seek preconception health advice. Methods: Using a descriptive qualitative approach, nonpregnant women (n = 31) aged 18‐45 years were purposively recruited to participate in a focus group (n = 7) that explored how preconception health is prioritised and how to increase women's awareness and uptake of healthy lifestyle behaviours in the preconception period. Focus group transcripts were coded by two researchers and an inductive process was used to categorise codes into themes. Results: Two themes and five sub‐themes relating to the aims of this study were identified. Participants believed preconception health to be important for all women, while admitting that was not a high priority if not planning a pregnancy. Participants suggested a range of interventions that spanned the social‐ecological model of health to engage preconception women in preventive actions and promote preconception health. These interventions included having access to reputable and easily accessible online sources of preconception health information, education and at secondary schools and public health campaigns. Conclusions: Future initiatives to engage preconception women should span the social‐ecological model of health and consider women's personal preferences for accessible and tailored preconception health information and support at individual, interpersonal, community and organisational levels, as well as in the broader environment. So what?: This research provides guidance to those in health promotion when planning future initiatives to promote and protect women's preconception health.